PENGARUH KOMPETENSI, INDEPENDENSI, DAN ETIKA AUDITOR TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK (KAP) DI JAKARTA - Siti Annisa Chosiana; Bani Saad (STIE Indonesia Banking School, 2014)
Public accountants are independent auditors that provide services to the general public, especially in audit of financial statements made by his client. Independent auditor has position as a third party within the client company. auditors have task and responsibility to audit client company based on financial statements made by management. Under these conditions, the public accountant (auditor) has an obligation to maintain the resulting audit quality.This research used simple random sampling to determine which sample to be used. This study uses a questionnaire as a method to gather data and likert scale to measure the score using a multiple linear regression model, and Statistical Product and Service Solution (SPSS) are use to calculate data. The results were as follows: (1) competence, independence, and ethics of the auditor affect the quality of audit partially. (2) independent variable that most affect the quality of audit is independence factor of auditor.